Aspectual construction V1take + prep to + V2infinitive and V1catch + prep to + V2infinitive in Portuguese: is this a case of linguistic variation? - Coelho, Sueli Maria (2015)
By adopting a diachronic perspective, whose analysis was based on quantitative and  qualitative  criteria,  this  study  has  investigated  the  hypothesis  that  the aspectual  auxiliary  constructions  constituted  by  the  verbs  to  catch  and  to take + preposition to + V2infinitive, although they score more than one aspectual configuration  in  Portuguese,  they  are  not  linguistic  variants.  The  research outcomes have confirmed the mooted hypothesis, as well as showing that the aspectual construction whose V1 is the verb to take is the oldest and the most productive in Portuguese. Although there may be contexts of neutralization, the analysis has also revealed that both constructions differ from each other in the connotation of the durational aspect.